دراسة مورفولوجية وبيولوجية للحشرة القشرية السوداء Saissetia oleae على الحمضيات في محافظة اللاذقية - أبوكف نبيل; محمد إياد; جزعة جابر (Latakia University Journal -Biological Sciences Series, 2016)
نُفذ هذا البحث في بساتين الحمضيات التابعة لمنطقة اسطامو بمحافظة اللاذقية خلال عامي 2014-2015. بيّنت نتائج الدراسة أن للحشرة القشرية السوداء جيلاً واحداً في السنة مع وجود جيل ثاني جزئي خلال فصل الصيف. تقضي الحشرة البيات الشتوي بطور الحورية في العمر الثاني وهو الطور الأكثر قدرة على تحمل الحرارة المنخفضة في فصل الشتاء. تعود الحورية بالعمر الثاني للنشاط في بداية فصل الربيع لتكمل دورة حياتها حيث تظهر الاناث الفتية في وقت مبكر من شهر نيسان على كل من الأفرع والأوراق، لتظهر الإناث البالغة مع بداية شهر أيار ويبدأ فقس البيض في منتصف هذا الشهر ويستمر حتى شهر تموز. تبيّن من الدراسة أن طور الحورية بالعمر الثاني هو الطور الأكثر تواجداً خلال الموسم على كل من الأفرع والأوراق. لوحظ موت أعداد كبيرة من الحشرة في طوري الحورية بالعمر الثالث وطور الأنثى الفتية والتي تطورت خلال الموسم نفسه، كما أظهرت دراسة توزع وانتشار الأطوار المختلفة للحشرة على الأجزاء النباتية أن الأفرع كانت أكثر إصابة من الأوراق مع تفوق معنوي في الكثافة العددية لتواجد طور الحورية والطور البالغ على الأفرع مقارنة مع الأوراق. This research carried out in the orchards of the Stamo area province of Lattakia citrus during the years 2014-2015, and the results of the study showed that the insect black cortical one generation per year with a second partial generation during the summer. Under the insect overwintering nymph stage in the second age is the most able to withstand the low-temperature phase in the winter. Mermaid back age-second activity in the beginning of spring to complete their life cycle where the female young appear in early April on each of the branches and leaves, to show adult females with the beginning of the month of May and starts the eggs to hatch in the middle of this month and will continue until the month of July. The study found that the nymph stage second phase age is the most common during the season at each of the branches and leaves. Observed the death of large numbers of the insect in the phasic nymph third age and female fledgling stage, which evolved during the same season, as the study of the distribution and the spread of the different phases of the insect on the plant parts showed that the branches were more injury than securities with higher than moral in the population density of the presence of eccentric nymph and adult stages the branches compared with the leaves.